Issues of electronic payment system and their impact on the effectiveness of business operations in iriga city - Balang, Shiena Rose P. (San Miguel, Iriga City: University of Saint Anthony, 2024)
Issues of electronic payment system and their impact on the effectiveness of business operations in iriga city.
Includes bibliographical references.
English
Keywords: Operations